2017
DOI: 10.1017/s0007114516004402
|View full text |Cite
|
Sign up to set email alerts
|

Supplementing the maternal diet of rats with butyrate enhances mitochondrial biogenesis in the skeletal muscles of weaned offspring

Abstract: The present study aimed to investigate the effects of maternal dietary butyrate supplementation on energy metabolism and mitochondrial biogenesis in offspring skeletal muscle and the possible mediating mechanisms. Virgin female rats were randomly assigned to either control or butyrate diets (1 % butyrate sodium) throughout gestation and lactation. At the end of lactation (21 d), the offspring were killed by exsanguination from the abdominal aorta under anaesthesia. The results showed that maternal butyrate sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…Furthermore, the therapeutic potential of increasing mtDNA content has been explored. For example, supplementation with butyrate in maternal diet was able to improve mtDNA content and increase mitochondrial activity in skeletal muscle from rat offspring48. Also, overexpression of PGC1α ameliorates muscular dystrophy in dystrophin-deficient mice49.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the therapeutic potential of increasing mtDNA content has been explored. For example, supplementation with butyrate in maternal diet was able to improve mtDNA content and increase mitochondrial activity in skeletal muscle from rat offspring48. Also, overexpression of PGC1α ameliorates muscular dystrophy in dystrophin-deficient mice49.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to inhibition of ectopic fat storage by reducing circulating lipid concentrations, SCFAs might also contribute to improvement in skeletal muscle insulin sensitivity by decreasing fatty acid synthesis and increasing lipolysis in skeletal muscle. SCFAs can increase the lipid-oxidation capacity of skeletal muscle by improving mitochondrial function [ 101 , 102 ]. Mitochondria are essential for maintaining energy homeostasis in skeletal muscle by adaptive reprogramming to meet the demands imposed by an increased lipid supply [ 103 ].…”
Section: Beneficial Effects Of Scfas On Energy and Glucose Homeostmentioning
confidence: 99%
“…Butyrate protected HepG2 cells against oxidation stress by modulating Nrf2 pathway activity and mitochondrial function. Huang et al [36] investigated the effect of maternal dietary butyrate supplementation on energy metabolism and mitochondrial biogenesis in offspring skeletal muscle and the possible mediating mechanisms. Their results indicated that maternal butyrate supplementation during the gestation and lactation periods influenced energy metabolism and mitochondrial biogenesis through the G-protein-coupled receptors and PPAR-coactivator-1α pathway in offspring skeletal muscle at weaning.…”
Section: Butyrate Inhibition Of Human Cancer Cellsmentioning
confidence: 99%